Physical Characterization of Turbot (Psetta Maxima) Originated Natural Hydroxyapatite - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2017)
Nowadays hydroxyapatite is one of the most popular biomaterials, which is used in various medical and dental applications areas as graft material. Bovine bone is the biggest source for natural hydroxyapatite production, but its production can lead to very dangerous disease, like mad cow disease, without high degree calcination. Hydroxyapatite produced from marine sources is much safer and easier to produce than bovine hydroxyapatite. Here in this study natural hydroxyapatite and related phases were produced from a local source turbot ( Psetta maxima). Beside the main bony internal structure, there are koshers (cycloid scale) on its skin. Koshers are bulky bumps, looking like flat, small and rounded structures. Internal bones and those bulky bumps were cleaned from flesh with chemicals and calcined at 850 degrees C for 4 hours. After calcinations, especially those bulky bumps, were formed into mesoporous structures with very light bluish color. Those mesoporous structures can be used as natural mesoporous hydroxyapatite structures for bone grafting purposes. The internal bones have also formed hydroxyapatite. Scanning electron microscope and X-ray diffraction studies were performed. I this study it is found that the bones of turbot consist of hydroxyapatite and TCP related phases. The aim of this study is to produce natural hydroxyapatite structures from turbot scale with low carbon footprint, without harming the environment and without using complex chemicals.